2022
DOI: 10.1186/s12906-022-03650-w
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid effects on testis, sex hormones, oxidative stress, and apoptosis in the relative sterility rat model following busulfan administration

Abstract: Background Busulfan is an antineoplastic medication that is broadly utilized for cancer treatment. It affects the testicular function and leads to sterility. The present study aimed to evaluate the effects of ellagic acid on testicular tissue changes, sexual hormones, antioxidant defense system, and caspase-9 and Bcl2 gene expression in the busulfan-induced relative sterile rat model. Methods This is an interventional-experimental animal study that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Ceribasi et al (2012) indicated that this polyphenol not only exhibits antioxidant and antiapoptotic properties, but also it can chelate metal ions and, therefore, prevent ironand copper-catalyzed ROS generation. These and other authors reported a protective effect, when rats were treated with chemo-toxic compounds (Turk et al 2008;Ceribasi et al 2012;Rostami et al…”
Section: Discussionmentioning
confidence: 71%
“…Ceribasi et al (2012) indicated that this polyphenol not only exhibits antioxidant and antiapoptotic properties, but also it can chelate metal ions and, therefore, prevent ironand copper-catalyzed ROS generation. These and other authors reported a protective effect, when rats were treated with chemo-toxic compounds (Turk et al 2008;Ceribasi et al 2012;Rostami et al…”
Section: Discussionmentioning
confidence: 71%
“…Busulfan is an alkylating chemotherapeutic agent that prevents cell division [ 52 , 53 ]. However, its potential mechanism of action is very intricate and probably involves multiple biological processes, such as disruption of cellular redox equilibrium, proliferation, apoptosis, and autophagy [ 54 , 55 ]. We investigated short- and long-term busulfan-mediated damage and the corresponding MSC-mediated rescue of human small intestine epithelium in our co-culture system.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that long-term culture of small intestine organoids after treatment with busulfan decreases both the size and the number of organoids. The reduced number of organoids might be a consequence of an oxidative stress induction by busulfan [ 54 ], which results in a delayed increase in cell death. However, the late adverse effect of other pathways activated by busulfan cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Busulfan is an alkylating chemotherapeutic agent that prevents cell division [48,49]. However, its potential mechanism of action is very intricate and probably involves multiple biological processes, such as disruption of cellular redox equilibrium, proliferation, apoptosis, and autophagy [50,51]. We investigated short-and long-term busulfan-mediated damage and the corresponding MSC-mediated rescue of human small intestine epithelium in our co-culture system.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that long-term culture of small intestine organoids after treatment with busulfan decreases both the size and the number of organoids. The reduced number of organoids might be a consequence of an oxidative stress induction by busulfan [50], which results in a delayed increase in cell death. However, the late adverse effect of other pathways activated by busulfan cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%